Specific Partial Reduction of Geranylgeranyl Diphosphate by an Enzyme from the Thermoacidophilic Archaeon Sulfolobus acidocaldarius Yields a Reactive Prenyl Donor, Not a Dead-End Product - Sato, Sho (American Society for Microbiology (ASM), 2008)
Geranylgeranyl reductase from Sulfolobus acidocaldarius was shown to catalyze the reduction of geranylgeranyl groups in the precursors of archaeal membrane lipids, generally reducing all four double bonds. However, when geranylgeranyl diphosphate was subjected to the reductase reaction, only three of the four double bonds were reduced. Mass spectrometry and acid hydrolysis indicated that the allylic double bond was preserved in the partially reduced product derived from geranylgeranyl diphosphate. Thus, the reaction product was shown to be phytyl diphosphate, which is a substrate for archaeal prenyltransferases, unlike the completely reduced compound phytanyl diphosphate.